UTILITY NFT - Yuliya Kharitonova (International Journal of Law in Changing World, 2023)
With the popularity of metaverse, the number of questions about the legal framework of utility tokens has also grown. In this area, the application of blockchain allows us to generalize the experience of tokenization of services. A countertrend is the evolution of NFTs from digital image right authentication to a utility solution that allows consumers to benefit from the possession of rights in the community. A legal analysis of utility NFTs in the metaverse leads to the need to apply the provisions of securities law to tokenization services. However, possessing the features of digital rights, utility NFTs cannot always be the investment, which requires the exclusion of such tokens from the scope of regulation of the law on crowdfunding.